Deception Reality: Street Magic from Blaine to Dynamo. Issue 1 (1st April 2015) - Sexton, Max
Abstract : Television has, throughout its history, used a mode that was founded on liveness as an assertion of its ability to relay an untransformed event. This essay explores the tension between the unmediated' reality' suggested by the television reality show, and the deception of 'street magic', popularised by the American David Blaine and the British magician, Dynamo. This tension can be understood as a sign of the intermediate space between fact and fiction, and, in turn, the parataxis of live and mediated forms within television.